MO229PROFILE OF TUBERCULOSIS AND ITS MANAGEMENT IN CHRONIC KIDNEY DISEASE. (29th May 2021) - Datta, Divya; Prabhu, Ravindra Attur; Rao, Indu Ramachandra; Shenoy, Srinivas Vinayak; Nagaraju, Shankar Prasad; Bhojaraja, Mohan V; Khader, Nisha Abdul
Abstract: Background and Aims: Estimates of Tuberculosis(TB) burden indicate an estimated incidence and mortality of 199 and 32 respectively per 100000 in our country. Risk factors for acquiring TB disease include HIV infection, Diabetes Mellitus, Tobacco consumption and undernutrition. We retrospectively studied profile of TB in Chronic Kidney disease(CKD) in our population. Method: Retrospective case record based study of consecutive TB patients visiting a Tertiary care hospital attached to a Medical College diagnosed by standard methods to demonstrate TB bacilli in sputum or affected tissue. CKD was diagnosed based on estimated Glomerular filtration rate less than 60 ml/min/m 2 for at least three months. Pattern of TB and adverse drug effects were studied. Statistical analysis was done on SPSS version 20 Results: Over ten months, of 746 TB patients seen, 41(5.4%) had CKD, Stage 3b, 4 and 5 in 7/41(17.1%), 11(26.8%), 23(56.1%) respectively. Among CKD 24(58.5%) had Diabetes Mellitus, 1(2.4%) HIV and 37(90.2%) hypertension. Pattern of TB is shown in table 1. Adverse drug reactions were significantly higher in CKD 24/41(54.5% vs 17% in non CKD, P < 0.05). Mortality in CKD was 3/41(7.3%) and not significantly higher on multivariable analysis than in those without CKD. Conclusion: In this retrospective survey of TB patients CKD constituted 5.4%, was associated with more adverse drug reactions but did not impact on mortality. Pulmonary TB was the common pattern in CKD.